Pengaruh Kepemimpinan Dan Disiplin Kerja Serta Motivasi Kerja Terhadap Kinerja Karyawan Bank Kalteng Cabang Kapuas - Hayes Hendra; Irwansyah Irwansyah; Taharuddin Taharuddin (Universitas Lambung Mangkurat, 2016)
The purpose of this study wast oexamine the partial and simultaneous influence of Leader ship, Work Discipline and motivation on employees performance of Central Kalimantan Bank Kapuas Branch. The sample population were all employees of the Bank namely 27 people. How ever, only 26 people taken as samples (a branch leader as an exception). Based on data organization structure per June 30, 2014. The research applied saturated sampling method since the sample were less than 30 people. The research used multiple linier regression analysis model. The results of the analysis showed that Leadership, Work Discipline and Motivation have significant effect partially and simultaneoes lyto the Employees Performance of Central Kalimantan bank Kapuas Branch. The Leadership was at 40.4%, Discip line 37.2% and Motivation was at 27.5%, mean while the simultaneous influence was at 68.5%. Keywords: Employee Performance, Leadership, Discipline and Motivation.